PENGARUH KONSENTRASI EKSTRAK WORTEL (Daucus carota L.) DALAM FORMULASI LOTION TERHADAP EFEKTIVITAS PENCERAHAN KULIT - Fitri, Ely Nurul; Nawangsari, Desy; Kurniasih, Khamdiyah Indah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Carrot (Daucus carota L.) is a natural source rich in β-carotene, an antioxidant compound that may inhibit melanin formation through the tyrosinase inhibition mechanism. This study aimed to determine the effect of varying concentrations of carrot extract in lotion formulations on skin-brightening effectiveness. This experimental laboratory study used four lotion formulations: a negative control, Formula 1 (5%), Formula 2 (10%), Formula 3 (15%), and a positive control (Kojie San® commercial lotion). The formulations were evaluated for physical characteristics (organoleptic, homogeneity, pH, spreadability, adhesion, and viscosity), safety through skin irritation testing, and skin-brightening effectiveness using a human skin tone set for 14 days on 25 female respondents. The results showed that all formulations met the physical property parameters, except for spreadability and adhesion, which were below the standard. No skin irritation was observed. Based on the skin-brightening test, 16% of respondents showed an improvement in skin brightness after 14 days of application, with Formula 3 (15%) exhibiting the highest effect, where 8% of respondents experienced a one-level increase on the skin tone scale compared to other formulations and the negative control. It can be concluded that the variation in carrot extract concentration affected the skin-brightening effectiveness, with the 15% formulation showing the highest result. These findings indicate that β-carotene in carrot extract has potential as a safe and effective natural active ingredient in cosmetic skin-lightening formulations.